Synthesis and characterization of Prussian blue analogue and layered transition metal oxide cathodes for high performance sodium-ion batteries / Chen Yuncai - Chen , Yuncai (2023)
Energy storage must be applied to these renewable energies, such as solar, wind, and tidal energy, due to their intermittent nature. The sodium-ion battery is one of the most competitive candidates due to its low cost and abundant availability of sodium. In this study, we focus on the cathode materials, namely Prussian blue analogues and P2-type transition metal oxides. Na-rich PB-4M was synthesized by controlling the concentration of Na+ ions during the synthesis process. PB-C with the cage-like porous structure was synthesized via the re-heating method and acid etching. P2-type transition metal oxide Na0.67(Li0.5Mg0.5)0.1(Ni0.33Mn0.67)0.9O2 (LMNM), with Li/Mg co-substitution, was synthesized via a solid-state method. TGA, (in-situ) XRD, FTIR, and SEM, GITT, CV were used to investigate the materials. PB-4M exhibited a specific capacity of 130 mAh/g at RT and 120 mAh/g at 80 ℃. At 80 ℃, PB-4M could still deliver a reversible specific capacity of 57 mAh/g at 2 C after 500 charge-discharge cycles. PB-C exhibited a specific capacity of 112 mAh/g at 0.2 C and 97 mAh/g at 10 C and no obvious capacity fading, with more than 80% capacity retention after the 1000th cycle. LMNM exhibited enhanced cycling performance with a reversible capacity of 127 mAh/g and a capacity retention of 75% over 100 cycles at 0.5 C.